Apartheid, 1948-1994 - Dubow, Saul 1959- (Oxford histories, 2014)
"This new study offers a fresh interpretation of apartheid South Africa. Emerging out of the author's long-standing interests in the history of racial segregation, and drawing on a great deal of new scholarship, archival collections, and personal memoirs, he situates apartheid in global as well as local contexts. The overall conception of Apartheid, 1948-1994 is to integrate studies of resistance with the analysis of power, paying attention to the importance of ideas, institutions, and culture. Saul Dubow refamiliarises and defamiliarise apartheid so as to approach South Africa's white supremacist past from unlikely perspectives. He asks not only why apartheid was defeated, but how it survived so long. He neither presumes the rise of apartheid nor its demise. This synoptic reinterpretation is designed to introduce students to apartheid and to generate new questions for experts in the field." -- Back cover